(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
Background Cataract is the major preventable cause of blindness. In India 50-80% of blindness is due to cataract. Recent data from World Health Organization (WHO) shows 25% decrease in blindness prevalence in India. Cataract surgery has been viewed as one of the most cost effective health interventions with a cost of disability adjusted life years saved each year being 20-40 (1200-1800 Indian Rs). There has been a substantial rise in cataract surgeries in recent years leading to increased utilization of drugs. Studies about pattern of drugs used in cataract patients are sparse in India. Hence the above study was taken up. Objective To analyze drug utilization in post cataract surgery patients based on WHO indicators. Materials and methods Across-sectional, observational study was conducted over a duration of 6 months at department of ophthalmology, Minto Eye Hospital, Bengaluru. A total of 110 prescriptions were analyzed who visited in-patient department. The data was analyzed by descriptive statistics. Results A total of 110 prescriptions were analyzed which included 431 drugs. Average number of drugs per prescription was 3.91, among which five drugs per prescription were maximum (41%). Majority of the drugs prescribed were in the form of eye drops (65.08%) and the commonest FDC eye drops prescribed being ciprofloxacin with dexamethasone (13.68%). Percentage of prescription with antibiotic is (52%) and injections were (0.89%). About (94.54%) of the drugs were prescribed by brand name and only (5.4%) by generic name. Percentage of drugs prescribed from essential drug list (72.92%). Commonly prescribed drugs were Antimicrobials (52%), Analgesic (23%), Steroid (7%), FDCs (10%), Mydriatics (4%) and others (4%). Conclusion Topical drugs were commonly prescribed to treat ocular infections. Evaluation of drugs using WHO core prescribing indicators showed that the number of drugs prescribed by generic names and from NLEM was low.